The Impact of Both Types of Leukemia on the Concentrations of Alpha-TNF and serum C and Serum Immunoglobulin in Both Sexes - Thamer Ismail Ahmed1, Mounif Saab Ahmed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Vascular leukemia is a malignant disease that affects the tissues that form the blood cells. These cells are carcinogenic and occur due to the deficiency of cells to differentiate and develop to be normal blood cells. The acute leukemia includes two types of acute and chronic, the seriousness of the disease on human life and its ability to infect all age groups, Gender The research is demonstrated to evaluate the level of tumor necrosis factor, active C protein and total white blood cells and their types in the blood of the study groups (leukemia patients and control) The research is conducted in the period from September 2018 until the end of April 2019 in the center of the province of Kirkuk specialized for tumors and blood diseases. Blood samples are collected from 141 patients with leukemia and 30 normal subjects (control group) in different age groups.